CHARACTERISTICS OF LIGHTWEIGHT CONCRETE USING THE AGGREGATE ROUGH LATERITE GRADING CONTINUOUS AND SIZE 10 MM - HERMAN, SURYANTO (KURVA S JURNAL MAHASISWA, 2016)
In an effort to utilize laterite stone, laterite stone was developed as coarse aggregate in the concrete mix to obtain concrete products are strong and stable. This study was conducted to determine whether the laterite stone can be used as an alternative material of coarse aggregate in the concrete mix, especially because of the abundance of coarse aggregate material laterite stone and underutilized. This research is also expected to be the basis for further research studies. Lateritic stone coarse aggregate material can be used as an alternative material of coarse aggregate in the concrete mix. Based above, the authors conducted research characteristics of lightweight concrete using laterite stone coarse aggregate material.This research uses mixed design method (Standard National Indonesia) SNI 03-2847-2002 conducted in the laboratory using the maximum size of coarse aggregate that is 40 mm. Samples that are used for concrete continuous gradations and concrete uniform of size 10 mm each using 30 sample and the total number of samples is 60 samples.            From the test results Compressive Strength Concrete and Concrete Continuous Gradient Uniform size of 10 mm using laterite stones and sand Mahakam, was able to achieve the planned Compressive Strength is f'c = 125 Kg / Cm2. Testing the compressive strength of on average to be achieved (f'cr) on concrete continuous gradation = 182.42 Kg / cm2. Compressive strength testing plan (f'c) onconcrete uniform size 10 mm = 176.61 Kg/cm2. Testing compressive strength average which is about to be achieved (f'cr) on concrete uniform size 10 mm = 146.26 Kg/cm2.